Utilizing WAMMI Components to Evaluate the Usability of E-commerce Website - Ahmad, Azizah; Hussain, Azham; Flayyih, Omar Hamid; Abdulwahab, Wasan; Sabri, Manhal Isam (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2017)
With the advance and the spread of communication devices, users are increasingly interacting with the applications on the Internet. This modern technology has been widespread and many industries are utilizing it, such as ecommerce. The literature stated that, any technology/products that are developed, it should be first accepted by its users. Broadly, user’s positive or negative attitude will affect the acceptance of new technology/products. Usability of the website is a strong predictor of the user satisfaction and intention to use. However, in recent years, the number of online stores has grown exponentially and it creates a strong rivalry between those stores. Therefore, poor website design can drive away potential customers. This study undertakes the ABC (not real name) commercial website as a case study. Unfortunately, until recently, the number of visitors who are visiting the ABC website has been a steep declined compared to other marketing websites. Consequently, the current empirical study strives to assess the usability of the ABC website based on the WAMMI components and the participants viewpoint. The results indicate that, attractiveness is satisfactory for the visitors of the website. In turn, each of controllability, efficiency, helpfulness and learnability are not satisfactory for the visitors.